2003
DOI: 10.1242/jeb.00183
|View full text |Cite
|
Sign up to set email alerts
|

Measuring wing kinematics, flight trajectory and body attitude during forward flight and turning maneuvers in dragonflies

Abstract: Details of the kinematics of free flight are very important to understanding insect flight mechanics. Important data for aerodynamic analysis and modeling include flight trajectory, body attitude and wing kinematics for individuals flying over a diverse array of behaviors, such as hovering, climbing and turning.A number of recent studies have focused on the kinematics of hovering and forward flight, using a variety of techniques. Azuma and Watanabe (1988) changed the velocity of the wind tunnel in their measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 15 publications
8
128
0
Order By: Relevance
“…3) presented in Wang and Sun [37] with the hind-wing leading the forewing in a phase of 180 o . Two kinematics of the motion were simulated: one is for rigid wings; the other is for flexible wings with camber deformation according to the data measured by Wang and Zeng [38]. The scattered camber deformation data during one flapping cycle are fitted into a curve as shown in Fig.…”
Section: B Application To 3d Dragonfly Model In Forward Flight With mentioning
confidence: 99%
“…3) presented in Wang and Sun [37] with the hind-wing leading the forewing in a phase of 180 o . Two kinematics of the motion were simulated: one is for rigid wings; the other is for flexible wings with camber deformation according to the data measured by Wang and Zeng [38]. The scattered camber deformation data during one flapping cycle are fitted into a curve as shown in Fig.…”
Section: B Application To 3d Dragonfly Model In Forward Flight With mentioning
confidence: 99%
“…The angle of attack for a moth of species Helicoverpa armigera was reported for variation in range from 35 to 160 [12]. Wang et al [22] reported the torsion angle of a dragonfly wing but they only indicated the torsion angle in the middle wings. The beetle had larger amplitude and more significant variation in the angle of attack along the spanwise direction.…”
Section: Hind Wing Flexibilitymentioning
confidence: 99%
“…The significance of wing camber deformation was evident in a wide range of insect groups, such as dragonfly [22] , moth [12] , honeybee [34] , locust [23] , and hover fly [23] . However, the investigation of change in the camber along the spanwise direction has been limited.…”
Section: Hind Wing Flexibilitymentioning
confidence: 99%
See 2 more Smart Citations